From hybrid space to dislocated space: Mobile virtual reality and a third stage of mobile media theory. (January 2019) - Saker, Michael; Frith, Jordan
Research in the field of mobile communication studies (MCS) has generally moved away from focusing on how mobile phones distract users from their physical environment to considering how the experience of space and place can be enhanced by locative smartphone applications. This article argues that trajectory may be complicated by the emergence of a new type of mobile technology: mobile virtual reality (MVR). While an increasing number of handsets are specifically developed with MVR in mind, there is little to no research that situates this phenomenon within the continuum of MCS. The intention of this paper is accordingly twofold. First, the article conceptualizes MVR as a connective tissue between the two sequential tropes of MCS: physical distraction and spatial enhancement. Second, the article introduces the concept of 'dislocated space' as a way of understanding the embodied space MVR might configure.